CONE NOZZLE ON VENTURY SCRUBBER TO REDUCE EMISSIONS OF PORTABLE INCINERATOR - Agung Sudrajad; Mekro Permana Pinem; Ni Ketut Caturwati; Venida Alan Devara (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2025)
Suboptimal waste wede168 management in Indonesia has resulted in increased exhaust emissions from the incineration process. One solution to reduce these emissions is the use of ventury wet scrubber technology, which functions to capture harmful particles and gases with water flow. This study aims to determine the effect of using a cone nozzle on the ventury wet scrubber on reducing incinerator exhaust emissions. The method used was to compare two conditions: incinerator without scrubber and incinerator with scrubber equipped with four cone nozzles. Emission parameters measured include CO, CO₂, HC, and O₂ using a gas analyzer. The results show that the system with cone nozzles can reduce CO emissions by 80.60%, CO₂ by 70.56%, and HC by 73.81%, and increase O₂ levels by 23.43%. Although CO emissions still slightly exceed the emission standard threshold (733 mg/Nm³ compared to the standard 625 mg/Nm³), the reduction achieved is very significant at 80.60%. Thus, the use of a cone nozzle on the ventury wet scrubber proved effective in reducing incinerator flue gas emissions.